Avaliação da resposta imune em suínos imunizados com o antígeno recombinante P42 visando a indução da proteção contra Pneumonia Enzoótica Suína - Jorge, Sérgio (2014)
Mycoplasma hyopneumoniae is the etiological agent of enzootic pneumonia (EP), a contagious respiratory disease that affects swine production worldwide. M. hyopneumoniae colonizes the ciliated epithelial cells of the respiratory tract, damaging the cells and predisposing the infected animals to secondary infections, causing significant economic losses. The commonly used vaccines to control this disease consist of inactivated whole cells (bacterins). These bacterins provide only partial protection and do not prevent the colonization of M. hyopneumoniae on the epithelial cells. Efforts to develop a more effective vaccine against mycoplasmas have been proposed and vaccines developed using recombinant DNA technology represents a promissing alternative. Although the genomes of four strains of. M hyopneumoniae have been sequenced, few recombinant antigens have been evaluated as candidate vaccines. Our research group produced and evaluated the immunogenicity and antigenicity of 35 secreted recombinant proteins and 6 transmembrane recombinant proteins. Some of these proteins were identified as having the potential to be used as vaccine antigens, including the molecular chaperone DnaK (P42 heat shock protein). The aim of this study was to assess the potential of recombinant P42 in vaccine preparations against EP, using swine animal model housed under field condictions in a M. hyopneumoniae-positive farm. Both, humoral and cellular immune responses were elicited when rP42 was delivered in Phosphate buffer saline, when combined to an oil based adjuvant, and when added to a whole cell vaccine preparation. The results indicate that immunization with rP42 emulsified in oil based adjuvant is able to induce antibodies against M. hyopneumoniae as well as the expression and the anti-inflammatory cytokine IL-10 in pigs. These immunogenic properties make recombinant antigen P42 a promising candidate for a recombinant subunit vaccine against EP.